1991
DOI: 10.1149/1.2085915
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Conductive Polymeric Nickel(II) Tetrakis(3‐methoxy‐4‐hydroxy‐phenyl)Porphyrin as an Anodic Material for Electrocatalysis

Abstract: Highly conductive film has been obtained by oxidative polymerization of nickel(II) tetrakis(3-methoxy-4-hydroxyphenyl)porphyrin, Ni(II)TMHPP. This material was characterized by voltammetry, ac impedance, UV-visible spectroscopy, and x-ray photoelectron spectroscopy. The application of polymeric Ni(II)TMHPP as an anode for catalytic oxidation of water, methanol, and hydrazine in basic media is discussed.) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 32 publications
7
28
1
Order By: Relevance
“…The Ni 2p spectrum of the NiTSPP monomer consists, as (Table 4), these values being similar to those for other Ni porphyrins. [22][23][24] The weak satellite at 863.1 eV is also in agreement with the literature. 25 The absence of strong shakeup satellite structure confirms the diamagnetic nature of Ni(II) in the TSPP monomer.…”
Section: X-ray Photoelectron Spectroscopy (Xps)supporting
confidence: 91%
“…The Ni 2p spectrum of the NiTSPP monomer consists, as (Table 4), these values being similar to those for other Ni porphyrins. [22][23][24] The weak satellite at 863.1 eV is also in agreement with the literature. 25 The absence of strong shakeup satellite structure confirms the diamagnetic nature of Ni(II) in the TSPP monomer.…”
Section: X-ray Photoelectron Spectroscopy (Xps)supporting
confidence: 91%
“…The representative example of such electrodes are those in which Ni(II)cyclam and other similar Ni(II)tetraazamacrocyclic complexes [35,36], Ni(II)-tetramethyldibenzotetraaza (14)annulene [37], Ni(II)-curcumin complex [25], Ni(II)-vanillin porphyrin [38,39], Ni(II)-tetrakis(N-methylpyridinium)porphyrin and Ni(II)-tetrakis(4-sulfonatophenyl) porphyrin [40,41] complexes were used as modifiers. It has been suggested that such polymer coated electrodes, with a three dimensional (3D) dispersion of the reacting centers, offer an increased catalytic efficiency in comparison with those covered by films with two dimensional arrangement of the catalytic sites.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic voltammetric deposition was performed within the potential range from À0.2 V to 1.0 V at a scan rate of 200 mV s À1 . Ef®ciency of a poly-TMHPP-Ni coating (G 0:8À À 1:5 nmol=cm 2 [5]) was calculated from the peak area, which illustrates the oxidation of Ni being present in the growing poly-®lm. That was usually obtained after 13±15 cycles.…”
Section: Electroactive Surface Preparationmentioning
confidence: 99%